Performance Analysis of Financial Statements of PT. Unilever Indonesia, Tbk. - Ariahmand Saragih; Chintia Ni; Claudio Purba; Nita Lestari; Sabda Dian Nuraini Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze the financial operations of PT. Unilever Indonesia through an activity analysis of the company's financial ratios for 2020 and 2022. The research method used is a quantitative descriptive method with secondary data collected through library research. The results showed that the financial performance of PT. Unilever Indonesia, Tbk, as measured by financial ratios in the 2020–2022 period. Thus, this research suggests that PT. Unilever Indonesia, Tbk., improve financial, inventory, and accounts receivable management in an effort to improve the company's financial health and sustain the company in the future.